Pemanfaatan e-Dictionary Berbasis Android pada Vocabulary for Beginner dalam Meningkatkan Kualitas Pengajaran di Mosaic English Training Center Kampoeng Inggris Pare - Hamidah, Fitria Nur; Yanuarmawan, Dion; Sukya, Fadelis (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Vocabulary is an important part of learning English. There are many numbers of words and phrases that are studied by each individual In the English word learning system and meaning in Indonesian. Therefore, many English language experts present detailed descriptions of of vocabulary form in English, both English-Indonesian and Indonesian-English, which can be understood easily by the English user environment. In learning vocabulary, of course there is a level that studies several types of vocabulary, one of the vocabulary learners is beginners. In this case, instructors and learners in Mosaic English Training Center need to be introduced to e-dictionary in learning vocabulary. Instructors often use dictionaries or dictionary manuals so it needs a more modern application, e-vocabulary dictionary is needed in learning vocab in the Mosaic English Training Center. The purpose of this program is to improve the ability of the instructors and the quality of teaching so it can be applied to the teaching and learning process and facilitate learners in learning vocabulary in the Mosaic English English Training Center.